Impact of Duodopa on Quality of Life in Advanced Parkinson's Disease: A UK Case Series. (13th March 2013) - Foltynie, T.; Magee, C.; James, C.; Webster, G. J. M.; Lees, A. J.; Limousin, P.
Abstract : Treatment options in advanced Parkinson's disease (PD) include subcutaneous apomorphine, pallidal or subthalamic nucleus Deep Brain Stimulation (DBS), or levodopa/carbidopa intestinal gel (LCIG/Duodopa). In this study, we describe the outcome of 12 PD patients with PD related complications started on LCIG, with respect to their quality of life measured by a disease specific validated scale—the PDQ39, together with diaries recording time spent "On, " "Off, " "Dyskinetic, " or "Asleep." At the time of latest follow up, improvements were observed in both the PDQ39 Summary index as well as diary reports of PD symptom control following introduction of LCIG, supporting its use in well selected patients. The use of a trial period of LCIG via naso-jejunal administration allows objective evaluation of improvement in PD symptom control in advance of the placement of the more invasive percutaneous jejunostomy procedure. The decision to embark on LCIG, apomorphine or DBS should be supported by input from centres with experience of all 3 approaches. Since LCIG is an expensive option, development of the most appropriate future commissioning of this therapy in the absence of Class 1 evidence requires careful scrutiny of the outcomes of its use in a broad range of published series.